FACTORS DETERMINING THE EFFECTIVENESS OF QUALIFYING YOUNG SWIMMERS FOR THE STAGE OF SPECIALIZED BASE TRAINING - Ruziyev Azimjon (Journals Park Publishing, 2022)
The article summarizes practical experience and theoretical knowledge on qualifying young swimmers for a specialized preparatory stage. In educational groups, factors affecting the coherence of teaching and the effectiveness of qualifying gifted children are considered.
Keywords: promising swimmers, swimmers’ selection, selection stages, specialized preparatory stage.